2002
DOI: 10.1038/sj.onc.1205246
|View full text |Cite
|
Sign up to set email alerts
|

Bloom's syndrome protein response to ultraviolet-C radiation and hydroxyurea-mediated DNA synthesis inhibition

Abstract: Bloom's syndrome (BS) arises through mutations in both copies of the BLM gene that encodes a RecQ 3'-5' DNA helicase. BS patients are predisposed to developing all the cancers that aect the general population, and BS cells exhibit marked genetic instability. We showed recently that BLM protein contributes to the cellular response to ionizing radiation by acting as downstream ATM kinase eector. We now show that following UVC treatment, BLM-de®cient cells exhibit a reduction in the number of replicative cells, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
33
0

Year Published

2002
2002
2017
2017

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 38 publications
(37 citation statements)
references
References 41 publications
(37 reference statements)
4
33
0
Order By: Relevance
“…We observed only partial checkpoint defects in him-6 C. elegans worms. Similarly, irradiation-induced apoptosis and G 2 /M cell cycle arrest is only partially compromised in human BS Ϫ/Ϫ cells (1,59). It was recently shown that HIM-6 physically interacts with the C. elegans ATR homolog, whose inactivation by RNAi leads to defective checkpoint processes in response to ionizing radiation (8), as well as to HU (A. Gartner, unpublished observation).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We observed only partial checkpoint defects in him-6 C. elegans worms. Similarly, irradiation-induced apoptosis and G 2 /M cell cycle arrest is only partially compromised in human BS Ϫ/Ϫ cells (1,59). It was recently shown that HIM-6 physically interacts with the C. elegans ATR homolog, whose inactivation by RNAi leads to defective checkpoint processes in response to ionizing radiation (8), as well as to HU (A. Gartner, unpublished observation).…”
Section: Discussionmentioning
confidence: 99%
“…sgs1-deficient budding yeast cells are partially defective in arresting S-phase progression in response to HU (15,66). Human BS Ϫ/Ϫ cells, on the other hand, respond normally to HU (1). S. pombe cells lacking the RecQ-like helicase Rqh1p also react normally to HU but are defective in the recovery from S-phase arrest when exposed to HU (53).…”
Section: Discussionmentioning
confidence: 99%
“…We performed the same experiments using wild type Priess and IPM1 BS lymphoblastoid cells, and we did not detect BLM proteolytic products (data not shown). Moreover, the strong decrease in expression of the full-length BLM protein in response to UVC radiation, which we previously described for D1 cells, 14 was also observed in K562 and Ramos cells (this study), and in Priess and IPM1 cells (data not shown). Thus, the UVC-induced decrease in BLM expression apparently does not correlate with the appearance of BLM proteolytic products.…”
Section: Discussionmentioning
confidence: 57%
“…1B), as expected. 14 Furthermore, 6 and 16 h post-UVC, the full-length BLM protein was totally degraded to a single band of about 110 kDa (∆BLM) in Ramos cells (Fig. 1B, upper middle panel), whereas no BLM cleavage was observed in UVCtreated D1 or K562 cells (Fig.…”
Section: Blm Expression In Response To Apoptosis Induction By Uvc or Humentioning
confidence: 99%
See 1 more Smart Citation